PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS,OPERATING CAPACITY DAN BIAYA AGENSI MANAJERIAL TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Yustika, Yeni; -, Kirmizi; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of liquidity, leverage, profitability, operating capacity and managerial agency cost on financial distress in manufacturing companies listed in Indonesia Stock Exchange 2011-2013. Purposive sampling method is used as a method of sampling, in order to obtain a sample of 18 companies. Technique of analysis data used logistic regression analysis. Based on the result of the research showed that liquidity, leverage and profitability that have significant impact on the financial distress. While operating capacity and managerial agency cost do not have a significant effect on the financial distress.Keywords: liquidity, laverege, profitability, operating capacity, managerial agency cost and financial distress.